Description of two new species of the genus Chlorogomphus Selys, 1854 (Odonata: Chlorogomphidae) and a new record of Chlorogomphus gracilis Wilson & Reels, 2001 from the Central Highlands of Vietnam - Phan, Quoc Toan; Karube, Haruki (European Journal of Taxonomy, 2022)
Two new species of the genus Chlorogomphus are described based on both sexes collected from the Central Highlands of Vietnam. These species are C. hoaian sp. nov. (holotype male from Kon Ka Kinh National Park, 14.3672° N, 108.5368° E, alt. 1000 m) and C. vani sp. nov. (holotype male from Chu Yang Sin National Park, 12.4780° N, 108.4617° E, alt. 749 m). Furthermore, C. gracilis Wilson & Reels, 2001 is recorded from Vietnam for the first time, with notes on its morphology and detailed illustrations of male and female structures.